2009
DOI: 10.2174/187153009787582397
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-Activated Protein Kinase: A Critical Node Linking Insulin Resistance and Cardiovascular Diseases in Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes is associated with insulin resistance, endothelial dysfunction and accelerated atherosclerotic diseases. Though underlying mechanisms remain to be unraveled, p38 mitogen-activated protein kinase (MAPK) appears to play important roles in their pathogenesis. As a member of the MAPK family, it regulates the activities of many transcription factors and proteins/enzymes and thus has a wide-spectrum of biological effects. Patients with insulin resistance and/or type 2 diabetes have high levels of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 128 publications
(128 reference statements)
5
54
1
Order By: Relevance
“…A study by Tanaka et al indicated that IKKβ induces both insulin action and diabetes, by a mechanism involving defective secretion in response to inflammatory cytokines (32). Another study showed that p38 MAP kinase is related to insulin resistance (22). Therefore, the lack of effects of JNK, IKKβ and p38 MAP kinase in the current study may suggest that deleterious actions associated with diabetes do not appear in Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 54%
“…A study by Tanaka et al indicated that IKKβ induces both insulin action and diabetes, by a mechanism involving defective secretion in response to inflammatory cytokines (32). Another study showed that p38 MAP kinase is related to insulin resistance (22). Therefore, the lack of effects of JNK, IKKβ and p38 MAP kinase in the current study may suggest that deleterious actions associated with diabetes do not appear in Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 54%
“…2,45,46 p38 MAPK plays a key role in hepatic glucose metabolism, 13 and ERK1/2 activation stimulates IRS-1 Ser 612 phosphorylation and thereby inhibits insulin signaling. 47 Consistent with reported hCRP activation of p38 MAPK and ERK1/2 in endothelial cells and macrophages, 10,48 we found that hCRP increased phosphorylated p38 MAPK and ERK1/2 ex vivo in liver tissues and in vitro in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…13 Moreover, JNK and ERK1/2 stimulate serine phosphorylation of IRS-1, an important mechanism that inhibits IRS-1-mediated insulin signaling. 14,15 The potential effect of hCRP on these pathways linking to insulin sensitivity remains elusive.…”
mentioning
confidence: 99%
“…Potentially this subsequently places the myocyte in a transient state of osmotic stress (Haussinger 1996). Intriguingly, in various cell types osmotic swelling has previously been shown to independently activate various signalling cascades known to be involved in cellular remodelling (Haussinger 1996;Liu and Cao 2009). It is interesting to speculate whether this type of osmotic stress could be a mechanism of adaptation with HIT.…”
Section: A Crucial Role For Glycogen Depletion?mentioning
confidence: 99%